Electrically-evoked oscillating calcium transients in mono- and co-cultures of iPSC glia and sensory neurons - Lawson, Jennifer; LaVancher, Elijah; DeAlmeida, Mauricio; Black, Bryan James (Frontiers in Cellular Neuroscience, 2023)
Activated glia are known to exhibit either neuroprotective or neurodegenerative effects, depending on their phenotype, while participating in chronic pain regulation. Until recently, it has been believed that satellite glial cells and astrocytes are electrically slight and process stimuli only through intracellular calcium flux that triggers downstream signaling mechanisms. Though glia do not exhibit action potentials, they do express both voltage- and ligand-gated ion channels that facilitate measurable calcium transients, a measure of their own phenotypic excitability, and support and modulate sensory neuron excitability through ion buffering and secretion of excitatory or inhibitory neuropeptides (i.e., paracrine signaling). We recently developed a model of acute and chronic nociception using co-cultures of iPSC sensory neurons (SN) and spinal astrocytes on microelectrode arrays (MEAs). Until recently, only neuronal extracellular activity has been recorded using MEAs with high signal-to-noise ratio and in a non-invasive manner. Unfortunately, this method has limited compatibility with simultaneous calcium transient imaging techniques, which is the most common method for monitoring phenotypic activity of astrocytes. Moreover, both dye-based and genetically encoded calcium indicator imaging relies on calcium chelation, affecting the culture’s long-term physiology. Therefore, it would be ideal to allow continuous and simultaneous direct phenotypic monitoring of both SNs and astrocytes in a high-to-moderate throughput non-invasive manner and would significantly advance the field of electrophysiology. Here, we characterize astrocytic oscillating calcium transients (OCa2+Ts) in mono- and co-cultures of iPSC astrocytes as well as iPSC SN-astrocyte co-cultures on 48 well plate MEAs. We demonstrate that astrocytes exhibit OCa2+Ts in an electrical stimulus amplitude- and duration-dependent manner. We show that OCa2+Ts can be pharmacologically inhibited with the gap junction antagonist, carbenoxolone (100 µM). Most importantly, we demonstrate that both neurons and glia can be phenotypically characterized in real time, repeatedly, over the duration of the culture. In total, our findings suggest that calcium transients in glial populations may serve as a stand-alone or supplemental screening technique for identifying potential analgesics or compounds targeting other glia-mediated pathologies.